Penerapan Model Pembelajaran Probing Prompting untuk Meningkatkan Kemampuan Eksplorasi Matematika dan Kepercayaan Diri Siswa - Ena Suhena Praja; Setiyani Setiyani; Neneng Aminah; Mudrika Mudrika; Laela Sagita (Faktor Jurnal Ilmiah Kependidikan, 2021)
This study aims to find out the increase of student’s ability in mathematical exploration, learning completeness, and the relationship between mathematical exploration abilities and students' self-confidence in the application of the probing prompting learning model. This is an experimental research method with One Group Pretest-Posttest Design. The data was collected by giving a test about mathematical exploration abilities and a questionnaire on self-confidence. The results of the study by applying the probing prompting learning model showed that there was an increase on student’s mathematical exploration ability at 0.806 with a high category. Students’ self-confidence achievement showed that there was no tendency towards the established self-confidence indicators. The achievement of individual learning completeness was ?75% and classical learning completeness was ? 75% in average. There is a relationship between mathematical exploration abilities and student self-confidence, the correlation coefficient is 0.204 with weak criteria.